2004
DOI: 10.1001/archneur.61.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Alzheimer Disease With the Interaction of MPO and A2M Polymorphisms

Abstract: The MPO and A2M polymorphisms are associated with sporadic AD in southern Italy. Moreover, a genomic interaction between these polymorphisms increases the risk of the development of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 17 publications
2
28
0
2
Order By: Relevance
“…Crawford et al [20] reported an increased risk of AD in Caucasians of both sexes carrying the -463 MPO-G/G genotype, but not in Hispanics, and Reynolds et al [21] also found that the -463 MPO-A allele in association with the apoE 4 allele increased the risk of AD only in Finnish men. Combarros et al [19] failed to detect any association between the MPO polymorphism and AD in a Spanish population, whereas Zappia et al [22] found an association between the -463 MPO-G/G genotype and SAD in a southern Italian population. In our Japanese case controls, we failed to detect any association between the MPO polymorphism and SAD.…”
Section: Discussionmentioning
confidence: 94%
“…Crawford et al [20] reported an increased risk of AD in Caucasians of both sexes carrying the -463 MPO-G/G genotype, but not in Hispanics, and Reynolds et al [21] also found that the -463 MPO-A allele in association with the apoE 4 allele increased the risk of AD only in Finnish men. Combarros et al [19] failed to detect any association between the MPO polymorphism and AD in a Spanish population, whereas Zappia et al [22] found an association between the -463 MPO-G/G genotype and SAD in a southern Italian population. In our Japanese case controls, we failed to detect any association between the MPO polymorphism and SAD.…”
Section: Discussionmentioning
confidence: 94%
“…73 In contrast, the A/A genotype was associated with increased risk of squamous cell carcinoma (OR ϭ 1.82, 95% CI ϭ 0.8 -4.1) and adenocarcinoma (OR ϭ 1.36, 95% CI ϭ 0.8 -2.5). 89 No significant association for the MPO genotype and patients with squamous cell carcinoma or adenocarcinoma was observed. 82 There was also no clear evidence of lung cancer risk by histologic types.…”
Section: Mpo G-463a Polymorphism and Lung Cancer Riskmentioning
confidence: 94%
“…These genes were described playing important roles in the immune system of animals (Hayashi et al, 2001;Magnadóttir et al, 2005;Magnadottir, 2010;Zappia et al, 2004). In relevance, a previous study reported that SNPs in A2M is related to the increasing risk for Alzheimer disease in human (Zappia et al, 2004). This suggests that the SNPs identified distributing in the immunerelated genes may play a crucial potential role involving in resistance or susceptibility to invasive pathogens of blunt snout bream.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the genes, A2M, TLR5 and C3 were found to be contained the highest number of SNPs. These genes were described playing important roles in the immune system of animals (Hayashi et al, 2001;Magnadóttir et al, 2005;Magnadottir, 2010;Zappia et al, 2004). In relevance, a previous study reported that SNPs in A2M is related to the increasing risk for Alzheimer disease in human (Zappia et al, 2004).…”
Section: Discussionmentioning
confidence: 99%